Risk Factors for Carbapenemase Producing-Carbapenem Resistant Enterobacteriaceae in Those With CRE Positive Cultures. (October 2020) - Wilson, Geneva; Pfeiffer, Christopher; Fitzpatrick, Margaret; Suda, Katie; Bartle, Brian; Rubin, Michael; Perencevich, Eli; Evans, Charlesnika
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) are gram-negative bacteria resistant to at least 1 carbapenem and are associated with high mortality (50%). Carbapenemase-producing CRE (CP-CRE) are particularly serious because they are more likely to transmit carbapenem resistance genes to other gram-negative bacteria and they are resistant to all carbapenem antibiotics. Few studies have evaluated risk factors associated with CP-CRE colonization. The goal of this study was to determine the risk factors associated with CP-CRE colonization in a cohort of US veterans. Methods: We conducted a retrospective cohort study of patients seen at VA medical centers between 2013 and 2018 who had positive cultures for CRE from any site, defined by resistance to at least 1 of the following carbapenems: imipenem, meropenem, doripenem, or ertapenem. CP-CRE was defined via antibiotic sensitivity data that coded the culture as being 'carbapenemase producing, ' being 'Hodge test positive, ' or 'KPC producing.' Only the first positive culture for CRE was included. Patient demographics (year of culture, age, sex, race, major comorbidities, infectious organism, culture site, inpatient status, and CP-CRE status) and facility demographics (rurality, geographic region, and facility complexity) were collected. Bivariate analysis and multiple logistic regression were performed to determine variables associated with CP-CRE versus non–CP-CRE. Results: In total, 3, 322 patients were identified with a positive CRE culture: 546 (16.4%) with CP-CRE and 2, 776 (83.63%) with non–CP-CRE. Most patients were men (95%) and were older (mean age, 71; SD, 12.5) and were diagnosed at a high-complexity VA medical center (65%). Most of the cultures were urine (63%), followed by sputum (13%), and blood (7%). Most were from inpatients (46%), followed by outpatients (42%), and long-term care facilities (12%). Multivariable analysis showed the following variables to be associated with CP-CRE positive cultures: congestive heart failure ( P = .0136), African American ( P = .0760), Klebsiella spp ( P < .0001), GI cancers ( P = .0087), culture collected in 2017 ( P = .0004), and culture collected in 2018 ( P < .0001). There were also significant differences CP-CRE frequencies by geographic region ( P < .001). Discussion: CP-CRE diagnoses are relatively rare; however, the serious complications associated make them important infections to investigate. In our analysis, we found that congestive heart failure and gastric cancer were comorbidities strongly associated with CP-CRE. In 2017, the VA formalized their CP-CRE definition, which led to more accurate reporting. Conclusions: After the guideline was implemented, CP-CRE detection dramatically increased in noncontinental US facilities. More work should be done in the future to determine the different risk factors between non–CP-CRE and CP-CRE infections. Funding: None Disclosures: None